ChemInform Abstract: Ligandless Palladium‐Catalyzed Regioselective Direct C—H Arylation of Imidazo[1, 2‐a]imidazole Derivatives. Issue 2 (23rd December 2015) - Grosse, Sandrine; Pillard, Christelle; Massip, Stephane; Marchivie, Mathieu; Jarry, Christian; Bernard, Philippe; Guillaumet, Gerald
Abstract: A wide range of 3, 6‐di(hetero) arylated title imidazole derivatives are obtained with good functional group tolerance by C‐3 pallado‐catalyzed functionalization performed with low catalyst loading.